Pengembangan Media Pembelajaran Virtumfi Pada Materi Penguraian Vektor Untuk Siswa SMA - Kurniawan, Fatah; Susilowati, Nisfullail Indah; Rusdiana, Dadi (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to develop a physics learning media on Vector Decomposition topic for high school students in grade X. The method used in this study is the 4D. The product obtained from this research and development is a learning media called VirtumFi: Vector. The data collection technique used observation and survey techniques, which the instruments were a media validity test questionnaire and a media practicality test. Then, the results of the questionnaire were analyzed to determine the criteria for the validity of the media and the percentage of the practicality of the media. After the practicality test and the validity test, the results of data analysis showed that the media had "valid" criteria with an average value of 3.46 and "practical" with an average percentage value of 79%. Based on the results of data analysis, the VirtumFi: Vector media developed in this study is valid and practical to be used. However, VirtumFi: Vektor is still considered less meaningful for physics learning in the Vector Decomposition sub topic. This is because of the shortcomings of the media. So that, students feel difficult to understand the concept of using VirtumFi media. Therefore, this article also aims to reveal the shortcomings of VirtumFi: Vektor. So that, it can be used by researchers and developers of physics learning media to develop further media